Znaczenie „dyplomacji demokracji” dla współczesnego Tajwanu (Politeja, 2023)
THE IMPORTANCE OF “DEMOCRATIC DIPLOMACY” FOR CONTEMPORARY TAIWANContemporary Taiwan is one of the leading democratic countries in Asia. The authorities in Taipei, under the leadership of President Tsai Ing-wen and the ruling Democratic Progressive Party have actively conveyed this message to the international community through their foreign policy since 2016. The objective of this paper is to examine the concept of “democracy diplomacy” in Taiwan, analyzing both scholarly discourse and observing Taiwan’s foreign policy. This strategic approach greatly bolsters Taiwan’s position among other nations that uphold democratic values, especially in the face of rivalries between major powers.